2001
DOI: 10.1515/bc.2001.200
|View full text |Cite
|
Sign up to set email alerts
|

Mig-6 Is a Negative Regulator of the Epidermal Growth Factor Receptor Signal

Abstract: In contrast to signal generation and transmission, the mechanisms and molecules that negatively regulate receptor tyrosine kinase (RTK) signaling are poorly understood. Here we characterize Mig-6 as a novel negative feedback regulator of the epidermal growth factor receptor (EGFR) and potential tumor suppressor. Mig-6 was identified in a yeast two-hybrid screen with the kinase active domain of the EGFR as bait. Upon EGF stimulation Mig-6 binds to the EGFR involving a highly acidic region between amino acids 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
162
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(169 citation statements)
references
References 74 publications
(58 reference statements)
3
162
2
Order By: Relevance
“…Despite its suppressive activity towards mitogenic and transforming signals triggered by ErbB-2 and EGFR, ectopically expressed RALT altered neither mitogenic responses of murine fibroblasts to serum nor cell transformation induced by v-ras and v-src (Fiorentino et al, 2000;Hackel et al, 2001). The issue of RALT specificity was further addressed in the experiments shown in Figure 1.…”
Section: Ralt Is Not a Promiscuous Rtk Inhibitormentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its suppressive activity towards mitogenic and transforming signals triggered by ErbB-2 and EGFR, ectopically expressed RALT altered neither mitogenic responses of murine fibroblasts to serum nor cell transformation induced by v-ras and v-src (Fiorentino et al, 2000;Hackel et al, 2001). The issue of RALT specificity was further addressed in the experiments shown in Figure 1.…”
Section: Ralt Is Not a Promiscuous Rtk Inhibitormentioning
confidence: 99%
“…Receptor-associated late transducer (RALT) has been recently identified as a feedback inhibitor of mitogenic signals propagated by ErbB-2 (Fiorentino et al, 2000) and EGFR (Hackel et al, 2001). RALT expression is activated by EGF, TGF-a and NRG-1 in fibroblasty and epithelial cells (Fiorentino et al, 2000), via a mechanism entailing transcriptional activation of the Ralt gene by the Ras-Raf-ERK pathway (Fiorini et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to ErbB-2 refractoriness to downregulation via the IDP (Marmor and Yarden, 2004), FI could represent a primary element of regulation of ErbB-2 signalling. We and others (Hackel et al, 2001) have identified RALT/MIG-6 as a feedback inhibitor whose activity is restricted to receptors of the ErbB family via still undefined mechanism/s. RALT expression is triggered by ErbB signalling via activation of the Ras-ERK pathway (Fiorini et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…RALT expression is triggered by ErbB signalling via activation of the Ras-ERK pathway (Fiorini et al, 2002). The RALT protein is in turn able to complex with activated ErbB RTKs and inhibit their signalling function in cultured cells (Hackel et al, 2001;Fiorini et al, 2002;Anastasi et al, 2003). In addition, a skin phenotype similar to that generated by a dominantnegative EGFR allele (Murillas et al, 1995) is observed in mice carrying a RALT transgene expressed by the K14 promoter (Costanza Ballaro`, Oreste Segatto and Stefano Alema`, manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%